2020
DOI: 10.1016/j.sopen.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Refusal of colorectal cancer surgery in the United States: Predictors and associated cancer-specific mortality in a Surveillance, Epidemiology, and End Results (SEER) cohort

Abstract: Introduction This study aims to understand patient factors associated with refusal of surgery for nonmetastatic colorectal cancer and the associated cancer-specific mortality. Methods Patients diagnosed with nonmetastatic colorectal cancer between 2004 and 2015 from the Surveillance, Epidemiology, and End Results Program were included. Results A total of 152,731 (99.4%) patients underwent surgery, and 983 (0.6%) refused surgery. Independent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…1,2 OS disparities between Black and White patients remained after controlling for patient characteristics. Consistent with previous findings in patients with colorectal, breast, or ovarian cancers,[7][8][9][10][11][12] patients with BC who forwent treatment recommendations experienced worse survival than those who received therapies. Furthermore, we found racial and ethnic disparities in OS stratified by treatment decision.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…1,2 OS disparities between Black and White patients remained after controlling for patient characteristics. Consistent with previous findings in patients with colorectal, breast, or ovarian cancers,[7][8][9][10][11][12] patients with BC who forwent treatment recommendations experienced worse survival than those who received therapies. Furthermore, we found racial and ethnic disparities in OS stratified by treatment decision.…”
supporting
confidence: 89%
“…[4][5][6] Studies have documented elevated risks of all-cause and disease-specific mortality in patients with cancer who forgo treatment recommended by their clinicians. [7][8][9][10][11] Previous research in colorectal, 8,9,11 ovarian, 12 lung, [13][14][15] or mixed cancer cohorts 16,17 has found that older age, racial and ethnic minority background (eg, Hispanic, non-Hispanic Asian or Pacific Islander, or non-Hispanic Black), low socioeconomic status, and late-stage presentations are associated with declination of therapies. For BC, several analyses have reported similar sociodemographic and clinical factors associated with treatment declination in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to surgery refusal in colorectal cancer patients ( 1 , 9 11 , 20 ). Surgery refusal rate for non-metastatic colorectal cancer is increasing over time, which increases colorectal cancer-specific mortality (adjusted HR: 5.10, 95% CI: 4.62-5.62) ( 20 ). Our study indicated that there was a significant black-white disparity in surgery refusal in non-metastatic colorectal cancer, which was largely mediated by patient's socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Those results suggested that hospital level is a key factor influencing patient's trust and decision in taking surgery. Much attention has been paid to surgery refusal in colorectal cancer patients (1,(9)(10)(11)20). Surgery refusal rate for non-metastatic colorectal cancer is increasing over time, which increases colorectal cancerspecific mortality (adjusted HR: 5.10, 95% CI: 4.62-5.62) (20).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data used in this study were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database (AYA site recode/WHO 2008 8.3 Carcinoma of trachea, bronchus, and lung) [ 27 , 28 ]. AYA is a site/histology recode used to analyze data on adolescent and young adults.…”
Section: Methodsmentioning
confidence: 99%